1958
DOI: 10.1073/pnas.44.9.889
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Structure of the Incompatibility Factors in Schizophyllium Commune

Abstract: The genetic nature of the incompatibility factors in the higher fungi has been the subject of considerable interest for many years. Multiple-allelic incompatibility systems of two types, bifactorial 1, 2 and unifactorial,3 were described in 1920-1924 and have since been found to be common in all groups of the Basidiomycetes except the rusts and possibly the smuts. The number of alternate factors at the incompatibility loci varies from ten or so in the Gasteromycetes 4, to a hundred or more in the Hymenomycetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1960
1960
1995
1995

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…No further distinction was made between the two recombinant A factors or the two recombinant B factors (Raper, Baxter and Middleton, 1958). A more detailed account of the genetics of S. commune can be found in Raper and Miles (1958).…”
Section: Methodsmentioning
confidence: 99%
“…No further distinction was made between the two recombinant A factors or the two recombinant B factors (Raper, Baxter and Middleton, 1958). A more detailed account of the genetics of S. commune can be found in Raper and Miles (1958).…”
Section: Methodsmentioning
confidence: 99%
“…Dr J. R. Raper (personal communication) and Raper, Baxter & Middleton (1958) claimed that the frequencies of the origin of new mating-type alleles by recombination in their stocks of Schizophyllum commune showed significant differences between crosses involving different wild strains. The greatest divergence occurred when a wild strain from California and another from New Guinea were crossed with local wild strains from Illinois.…”
Section: Heterogeneous Recombination Frequencies In Other Fungimentioning
confidence: 99%
“…He concluded that a cytoplasmic factor was involved. Preliminary tests with S. commune suggest that the choice of dikaryotising nuclei is directly influenced by the mating types involved and more particularly by the structure of the A and B alleles as described by Raper, Baxter and Middleton (1958). The problem of differential affinity between mating types is the subject of further experiments.…”
Section: Resultsmentioning
confidence: 99%